Inspiring the Spirit of Volunteering in the Halal Industry among Youths in Malaysia - Fazilah Idris; Fariza Md. Sham; Nurliana binti mohd.hassan (International Journal of Supply Chain Management, 2018)
Abstract The focus of halal industry is not merely the market but its about creating a conducive ecosystem upon approaching the market. That is the halal supply chain. Technically, the responsibilities are on the shoulder of Halal Executives (HEs). Nevertheless, most importantly is to ensure the industry players are aware and fully equipped with knowledge and skills in order to keep them at par to the Syariah law. As for today, it is crucial to make our youths as part of the team. They can make great contribution and collaboration to the entire industry by making themselves and others voluntarily energized and accessed to the halal certification matters. Unfortunately, it seems that they are not mentally and spiritually ready to adopt and adapt to the basic teachings of al-Quran specifically over the concept of halalan toyyiban. Too many of them are taking things too easily as the issue gets worst. Their concerns are more on lifestyles rather than learning styles. So, what does it takes to keep our youth updated to the reality of buying power? How can HEs be at their best to conduct their task? What drives a person to be committed and competent to the ummah? This concept paper of its kind may bring forward the famous theory of Planned Behaviour which has been practiced academically by the researchers of consumerism. By understanding it and getting the values fostered may enculture a proper, genuine and civilized volunteerism attitude among our youth. Keywords Volunteering, youth, halalan toyyiban, theory of Planned Behaviour, halal executive